Retratos do processo de escolarização na educação básica pública durante a pandemia de COVID-19: uma revisão sistemática da literatura - Mardegan, Eliana (2025)
This research aimed to conduct a systematic review of the literature, in dissertations and theses produced in Brazil, between 2020 and 2024, that address the schooling process in public basic education during the Covid-19 pandemic. The aim was to identify in the research studied how the teaching-learning process of basic education students occurred in its various manifestations and to reflect on its consequences. A mapping of the data was carried out in the Brazilian Digital Library of Theses and Dissertations (BDTD), using the descriptors “educando OR aluno OR aluno AND pandemia covid”, and 71 publications were found, most of them dissertations; after applying the exclusion criteria, 6 dissertations remained, whose contents met the objectives of this research. The data were organized based on the general characteristics of the research: objectives, method, results, analysis and discussion, for each dissertation, a reflective analysis and, then, a summary. Significant heterogeneity was observed among the studies in relation to participants (managers, teachers, staff and students), levels of education, data production and analysis procedures, lack of explicitness of a specific theoretical framework, but a list of authors who supported the analyses and discussions. The research data generally show the difficulties faced by teachers and students with remote teaching; on the part of teachers, the sudden change to the use of technologies for which they were not prepared, the need for adequate equipment and, in general, the lack of training and support; on the part of students, the difficulty in accessing adequate equipment and resources and adapting to the new condition were recurrent in the studies, with emphasis on early childhood education and students with disabilities. The results of this research show that it is necessary to conduct review studies with specific delimitations and, in particular, empirical research that addresses post-pandemic education, in order to identify possible consequences of remote teaching and the policies that have been (or not) adopted by education networks